1996
DOI: 10.1177/096032719601500609
|View full text |Cite
|
Sign up to set email alerts
|

HFA-134a (1,1,1,2-tetrafluoroethane): effects of inhalation exposure upon reproductive performance, development and maturation of rats

Abstract: 1 HFA-134a was administered to AHA rats by snout-only inhalation for 1 h daily to assess the effects of treatment on reproduction and development. 2 In a fertility study, rats were exposed to atmospheres of 2500, 10000 or 50000 p.p.m. HFA-134a throughout gametogenesis, mating, pregnancy and lactation. 3 In a peri- and post-natal study, rats were exposed to HFA-134a from days 17 to 20 of pregnancy and days 1 to 21 post partum to atmospheres of 1800, 9900 or 64 400 p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 11 publications
0
19
0
3
Order By: Relevance
“…There are several human and animal toxicology studies which have evaluated the safety of Tetrafluoroethane [11][12][13][14][15][16][17]. Tetrafluoroethane (TFE) has recently been introduced in dentistry, in the field of periodontics for depigmentation and it is being used in dermatology as a skin cooling medium in the laser therapy [7,18].…”
Section: Introductionmentioning
confidence: 99%
“…There are several human and animal toxicology studies which have evaluated the safety of Tetrafluoroethane [11][12][13][14][15][16][17]. Tetrafluoroethane (TFE) has recently been introduced in dentistry, in the field of periodontics for depigmentation and it is being used in dermatology as a skin cooling medium in the laser therapy [7,18].…”
Section: Introductionmentioning
confidence: 99%
“…A good example of such studies, were those conducted on HFA-134a as an alternative to chlorofluorocarbons for use in metred dose inhalers. Comprehensive preclinical inhalation toxicology study results indicated that HFA-134a was not considered toxic or oncogenic [173,174] and appeared to have no reproductive toxicity [175] and was therefore deemed a safe alternative. The potential of the lungs as a route of systemic administration of a drug will largely be determined by the toxicological implications of its inhalation and therefore good study design is critical.…”
Section: Inhalation Toxicology In Animalsmentioning
confidence: 99%
“…Substanzbedingte Befunde an den Organen traten nicht auf. Bei den F 1 -und F 2 -Tieren, die nicht selbst behandelt worden waren, zeigten sich keine substanzbedingten Effekte auf die Fertilität (Alexander et al 1996). In dieser Studie wurde für Effekte auf die Fertilität eine NOAEC von 50 000 ml 1,1,1,2-Tetrafluorethan/m 3 erhalten, wobei zu berücksichtigen ist, dass die Tiere nur eine Stunde pro Tag exponiert wurden.…”
Section: Fertilitätunclassified
“…Trächtigkeitstag und vom ersten bis zum 21. Laktationstag bei je 40 trächtigen AHA-Ratten keine maternal-und entwicklungstoxischen Wirkungen (Alexander et al 1996). Die Exposition gegen 1,1,1,2-Tetrafluorethan war mit einer Stunde am Tag sehr kurz und wurde zu einem sehr späten Zeitpunkt der Trächtigkeit begonnen, nachdem die Organogenese bereits abgeschlossen war.…”
Section: Entwicklungstoxizitätunclassified